A comunicação nas redes sociais digitais de suicidas do meio rural do Rio Grande do Sul - Gonçalves, Jana Rossato (2022)
Approximately 800,000 lives lost every year. In Brazil, this reality is no different, the country recorded more than 13,500 cases in 2019, being considered a public health problem. In the state of Rio Grande do Sul, the rates are high, even more so in rural areas. Suicide is considered a complex and multifactorial subject, which can affect anyone, of any age or social condition, with no specific cause that justifies its motivation. However, commonly the cases present some mental disorders, such as anxiety, depression, and also the signaling of intentions to people in the conviviality in periods that precede the fatality. Understanding the advancement of communication resources and the new dynamics of virtual relationships, these signs can also occur in the virtual environment. With this, the present work aimed to investigate the media communication built by suicidal users in digital social networks from their profile. The investigation of the cases took place in the period 2018 and 2020 from users of digital social networks who are residents of rural Rio Grande do Sul. The approach of the work permeated the research of the social field of quanti-qualitative, having as object of analysis the contents published in the personal profiles before the fatality. The relevant information that was collected are the characteristics of the users and their publications, considering that these may help to identify common parameters of behavior among suicides. Thus, it can contribute to the identification of a communication trend and the prevention of future cases. In conclusion, the present study found that in digital social networks, in most cases, there is no explicit speech about their intentions, but that there is a change in behavior and an implicit communication of deep suffering. Demonstrating that these communication channels can also be explored for suicide prevention.